A national overview of surgical misadventures in head and neck surgery: "Oh No, You Cut It". (7th May 2019) - Al‐Qurayshi, Zaid; Randolph, Gregory; Walsh, Jarrett; Owen, Scott; Kandil, Emad
Abstract : Objectives/Hypothesis: To examine the risk and prevalence of accidental intraoperative injury reported during head and neck surgeries and the associated outcomes. Study Design: Retrospective cross‐sectional analysis. Methods: An analysis utilizing the Nationwide Readmissions Database, 2010 to 2014. Adult patients with a reported accidental intraoperative injury were compared to controls without such injuries. Results: A total of 173 cases and 105, 659 controls were included. Most cases were reported in surgeries of the mouth/tonsils (29.4%) and maxillofacial bones/mandible (22.5%). The remaining cases were reported in surgeries of the pharynx/larynx (17.5%), nose/paranasal sinuses (15.4%), salivary glands and ducts (6.2%), thyroid/parathyroid (5.2%), and ear (3.8%). The multivariate logistic regression model demonstrated that surgeries of the pharynx/larynx were associated with the highest risk of injuries compared to other site surgeries (odds ratio [OR]: 2.51, 95% confidence interval [CI]: 1.49, 4.25, P < .001]. Concomitant neck dissection was also independently associated with the risk of injury (OR: 4.07, 95% CI: 2.05, 8.09, P < .001]. Compared to controls, cases were not associated with an increased risk of mortality ( P = .63) or readmission ( P = .29); however, those cases had a significantly longer hospital stay on average by 3.64 ± 0.95 days/case ( P < .001) and a higher cost of treatment on average by $13, 478 ± 119.42/case ( P < .001). Conclusions: This study reports on the prevalence and outcomes of accidental intraoperative injuries reported in head and neck surgeries. The prevalence is relatively low, and the annual trend appears stable; however, it is associated with a significant burden on the health system. Level of Evidence: NA Laryngoscope, 130:918–924, 2020